STRESS FRACTURES IN SPORT - Đivo Ban (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
Children and adolescents today, all before starting with regular sports activities and involvement in semi-professional and top professional sport, so it increases the num- ber of discovered stress fractures in this age. This type of injury can occur as a consequence of action one strong force, or the many repeated small force strength, to be exact, when the load (stress) transcend ability reparations bones. Stress fractures are recorded and described up to the lower limbs. Research has been confirmed that the bones of lower leg are mostly made in injury, and with the el- derly and with the population of children and young adolescents. Occur in many sports, something to them is greater when the frequency of running and often are present in the female population. According to the results of numerous investigations, mistakes in the training are the most common cause of the emergence of stress fracture. In a direct comparison with complemented these injuries is the condition of muscles, so it is important that at the sa- me time carry out exercises strengthen muscles and stretching. Typical clinical signs of stress fractures are localized painful sensitivity to palpa- tion and runoff in a small number of cases. The basic diagnostic procedure is a medical check, it is the small, radiology and scintigraphyc diagnostics (most accurate) and mag- netic resonance imaging. Treatment is usually without surgery and conservative, with rest and reducing stress, and its activity athlete breaks mainly between four and eight weeks. Only the very need surgical treatment The most important thing is that attention is focused on the proper prevention and to take all that it ever occurred to stress fractures that athletes ramble of the courts and the competition (better education of sports workers, separation of groups with increa- sed risk of the formation of an injury, adaptation activities age and abilities of athletes, adequate sports equipment, high-quality sports shoes and soft background on which the training).